Impact of Different Personal Protective Clothing on Wildland Firefighters' Physiological Strain - Carballo-Leyenda, Belén; Villa, José G.; López-Satué, Jorge; Rodríguez-Marroyo, Jose A. (Frontiers in Physiology, 2017)
Wildfire firefighting is an extremely demanding occupation performed under hot environment. The use of personal protective clothing (PPC) is needed to protect subjects from the thermal exposure. However, the additional use of PPC may increase the wildland firefighters’ physiological strain, and consequently limit their performance. The aim of this study was to analyze the effect of four different PPC on the physiological strain of wildland firefighters under moderate conditions (30ºC and 30% RH). Eight active and healthy wildland firefighters performed a submaximal walking test wearing a traditional short sports gear and 4 different PPC. The materials combination (viscose, nomex, Kevlar, P-140 and fire resistant cotton) used during the PPC manufacturing process was different. During all tests, to simulate a real scenario subjects wore a backpack pump (20 kg). Heart rate, respiratory gas exchange, gastrointestinal temperature, blood lactate concentration, perceived exertion and temperature and humidity underneath the PPC were recorded throughout tests. Additionally, parameters of heat balance were estimated. Wearing a PPC did not cause a significant increase in the subjects’ physiological response. The gastrointestinal temperature increment, the relative humidity of the microclimate underneath the PPC, the sweat residue in PPC, the sweat efficiency, the dry heat exchange and the total clothing insulation were significantly affected according to the PPC fabric composition. These results suggest that the PPC composition affect the moisture management. This might be taken into account to increase the wildland firefighters’ protection in real situations, when they have to work close to the flames.